2017
DOI: 10.18632/oncotarget.18336
|View full text |Cite
|
Sign up to set email alerts
|

Combination of platelet count and lymphocyte to monocyte ratio is a prognostic factor in patients undergoing surgery for non-small cell lung cancer

Abstract: The aim of this study was to investigate the usefulness of a novel inflammation-based prognostic system, called COP-LMR (combination of platelet count and lymphocyte to monocyte ratio), for predicting postoperative survival of patients with non-small cell lung cancer (NSCLC). COP-LMR was calculated on the basis of the obtained data. Patients with both an elevated platelet count (PLT) (>30 × 104mm-3) and a low LMR (<3.6) were assigned a score of 2, and patients with one or none of the parameters were assigned a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 31 publications
(36 reference statements)
1
22
1
Order By: Relevance
“…Our results showed that COP-LMR was an independent predictor for shorter overall survival and progression free survival in stage IV NSCLC. Liu et al have shown that COP-LMR has prognostic value in patients with NSCLC who underwent curative resection [ 21 ]. On the other hand, our study population were comprised of stage IV NSCLC patients with MPE.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our results showed that COP-LMR was an independent predictor for shorter overall survival and progression free survival in stage IV NSCLC. Liu et al have shown that COP-LMR has prognostic value in patients with NSCLC who underwent curative resection [ 21 ]. On the other hand, our study population were comprised of stage IV NSCLC patients with MPE.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, platelet counts are associated with cancer progression. The cutoff value of platelet counts has not been clearly defined yet, although platelet count of 30.0 x 10 4 mm -3 is often used in previous publications on prognostic value of platelet in cancer [ 21 , 35 ]. Consistent with these previous publications, the cutoff value of platelet count in our study was also 30.0 x 10 4 mm -3 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, long-term application of low-dose anti-platelet drugs, such as aspirin, inhibits cancer metastasis and significantly reduces cancer incidence [ 31 , 32 ]. Together these results suggest that platelet activation is a potential target and prognosis marker for cancer treatment [ 29 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 97%